Transformasi Perilaku Konsumen Akibat Adopsi Teknologi Digital Studi tentang Penggunaan E-Commerce dan Pembayaran Non-Tunai - Andry Irdyansah; Harini Harini; Nila Masalikul Masruroh (Joined Journal (Journal of Informatics Education), 2025)
This study aims to deeply analyze the transformation of consumer behavior triggered by the adoption of digital technology, specifically in the context of e-commerce utilization and non-cash payment. The digital era has reshaped the traditional buying cycle into a faster, more efficient, and personalized process. The research method employed is a systematic literature review of relevant studies within the last five years, supported by secondary data on the growth of digital transactions. The findings reveal a significant shift from conventional rational buying behavior towards behavior driven by convenience, information accessibility, and the personalized customer experience offered by digital platforms. The adoption of e-commerce and non-cash payment (such as mobile banking and e-wallets) not only affects the purchase stage but also alters the information search stage (dominated by online reviews) and the post-purchase evaluation (via ratings and feedback). The implication of this transformation requires businesses to implement omnichannel strategies and prioritize consumer data security to maintain loyalty in an increasingly competitive market.